Evolutionary Algorithms In Auction Models Of Service Procurement - Lee, Chen Wei (2019)
In combinatorial auction (CA) based winner determination problem (WDP) for transportation service procurement, carriers bid in packages according to lanes advertised by shipper. Along development of technologies and internet, last mile delivery, a service that needs fast decision is getting attention. However, previous researchers focused on solving mixed integer model for the CA based WDP, which is not efficient for large scale instance. Therefore, this research proposed an implementation of genetic algorithm (GA) with knowledge based operators as an alternative to approximate the solution.